2011
DOI: 10.1105/tpc.111.087239
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between N-Terminal Methionine Excision and FtsH Protease Is Essential for Normal Chloroplast Development and Function in Arabidopsis    

Abstract: N-terminal methionine excision (NME) is the earliest modification affecting most proteins. All compartments in which protein synthesis occurs contain dedicated NME machinery. Developmental defects induced in Arabidopsis thaliana by NME inhibition are accompanied by increased proteolysis. Although increasing evidence supports a connection between NME and protein degradation, the identity of the proteases involved remains unknown. Here we report that chloroplastic NME (cNME) acts upstream of the FtsH protease co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 76 publications
2
39
1
Order By: Relevance
“…CV targeted PsbO directly and might alter the structure of the PSII complex, removing PsbO ( Figure 7G), affecting PSII stability, and making core proteins (such as D1) more susceptible to thylakoid proteases. The proteases Deg (Kapri-Pardes et al, 2007) and FstH (Lindahl et al, 2000;Zaltsman et al, 2005;Shen et al, 2007;Adam et al, 2011) have been identified to be responsible for the turnover of D1. Interestingly, both DegP1 and FstH1 appeared to interact with CV (Supplemental Table 1), and FstH1-CFP colocalized with CV-GFP in vivo (Supplemental Figure 11B).…”
Section: Mediates Chloroplast Destabilization and Vesiculationmentioning
confidence: 99%
“…CV targeted PsbO directly and might alter the structure of the PSII complex, removing PsbO ( Figure 7G), affecting PSII stability, and making core proteins (such as D1) more susceptible to thylakoid proteases. The proteases Deg (Kapri-Pardes et al, 2007) and FstH (Lindahl et al, 2000;Zaltsman et al, 2005;Shen et al, 2007;Adam et al, 2011) have been identified to be responsible for the turnover of D1. Interestingly, both DegP1 and FstH1 appeared to interact with CV (Supplemental Table 1), and FstH1-CFP colocalized with CV-GFP in vivo (Supplemental Figure 11B).…”
Section: Mediates Chloroplast Destabilization and Vesiculationmentioning
confidence: 99%
“…Protein concentrations were measured with the two-dimensional Quant kit (GE-Healthcare Biosciences). After modified trichloroacetic acid/acetone precipitation (Espagne et al, 2007), the samples were brought up to equal volume and the fractions (supernatant:pellet = 1:1, ;1 mg) were resolved by long-range SDS-PAGE (14%) as previously reported (Fukata et al, 2004;Batistic et al, 2008) and analyzed by immunoblots using either anti-GFP or anti-H + ATPase antibodies (Abcam and Agrisera) as previously described (Adam et al, 2011). Band intensities were quantified with Quantity One software (Bio-Rad).…”
Section: Subcellular Fractionation and Immunoblot Analysismentioning
confidence: 99%
“…In eukaryotes, cotranslational N-terminal Met excision (NME) by Met aminopeptidases (MetAP) and N-aterminal acetylation (Nt-acetylation) catalyzed by N-terminal acetyltransferases (Nats) are two major protein modifications contributing to the diversity of protein N termini and to the N-end rule (Giglione et al, 2000(Giglione et al, , 2003Ross et al, 2005;Frottin et al, 2009;Gibbs et al, 2014a). Although limited studies have been conducted in plants on the N-end rule (Giglione et al, 2003;Graciet et al, 2009;Holman et al, 2009;Adam et al, 2011;Bienvenut et al, 2011;Gibbs et al, 2011Gibbs et al, , 2014bLicausi et al, 2011;Weits et al, 2014), recent genomic and N-terminal acetylome analyses in yeast, animals, and plants revealed that the NME and Nt-acetylation processes, along with the related enzymatic activities, are largely conserved through eukaryotic lineages (Polevoda et al, 1999;Arnesen et al, 2009;Goetze et al, 2009;Bienvenut et al, 2012;Liu et al, 2013). Particularly, in vivo and in vitro studies have shown that all MetAPs share similar substrate specificity, removing the first Met only when the second residue has a small radius of gyration of the side chain; on the contrary, bulky amino acids do not allow the removal of the first Met (Bienvenut et al, 2012).…”
Section: Introductionmentioning
confidence: 99%